Knowledge and Practices of Hairdressers about Occupational Safety and Health in Kaski District - Gopal Prasad Sedhai (Interdisciplinary Journal of Management and Social Sciences, 2025)
Hairdressers are exposed to various occupational hazards, including physical, chemical, and biological risks, which can lead to skin disorders, respiratory issues, and communicable diseases. This cross-sectional study assessed the knowledge and practices of hairdressers regarding occupational safety and health (OSH) in Kaski district, Nepal. A total of 60 salon workers from urban and rural areas were surveyed using a semi-structured questionnaire and direct observations. The findings revealed a satisfactory level of OSH awareness overall, with urban workers demonstrating significantly higher awareness compared to their rural counterparts. Most participants (83.3%) acknowledged the role of contaminated tools in spreading skin diseases, and 96.7% identified razors as potential sources of contamination. However, gaps in the use of personal protective equipment (PPE) and adherence to hygiene practices were observed, particularly among rural workers. Musculoskeletal disorders (MSDs) were prevalent due to prolonged standing and repetitive motions, highlighting the need for ergonomic training. Furthermore, the study emphasized the importance of training and education in improving OSH practices, as workers with formal training exhibited better safety practices. The findings align with global research, underscoring the urgent need for targeted interventions, stricter regulations, and comprehensive training programs to enhance workplace safety and health in the hairdressing profession. Future research should explore the long-term impacts of these measures to promote a safer working environment.